Analisis Studi Kelayakan Bisnis Coffe Shop “GALIH” di Kota Medan Melalui Berbagai Aspek - Vientiany, Dini; Baqis, Abelia Mita; Putri, Dinda Fitriyah Kholisoh Ahmadita; Fadilla, Tessa (Madani: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to analyze the business feasibility of Coffee Shop Galih in Medan City through a business feasibility study approach. The research method used is descriptive qualitative with data collection techniques in the form of observation, interviews, documentation, and mini surveys. The analysis was conducted on market and marketing aspects, legal aspects, technical and operational aspects, human resource management aspects, and environmental aspects. The results of the study show that Coffee Shop Galih has good market opportunities with clear segmentation and an effective social media-based marketing strategy. From a legal perspective, the business has basic legality as an MSME, although it does not yet have full halal certification. The technical and operational aspects show a strategic location, adequate facilities, and a well-functioning operational system. From a management perspective, the simple but effective organizational structure supports the smooth operation of the business. Additionally, from an environmental perspective, Coffee Shop Galih has implemented adequate cleanliness and waste management practices. Based on the analysis results, Coffee Shop Galih is deemed viable for operation and development, with ongoing improvements needed in certain supporting aspects.